Angiotensin-(1–7) as a Potential Therapeutic Strategy for Delayed Cerebral Ischemia in Subarachnoid Hemorrhage - Annoni, Filippo; Moro, Federico; Caruso, Enrico; Zoerle, Tommaso; Taccone, Fabio Silvio; Zanier, Elisa R. (Frontiers in Immunology, 2022)
Aneurysmal subarachnoid hemorrhage (SAH) is a substantial cause of mortality and morbidity worldwide. Moreover, survivors after the initial bleeding are often subject to secondary brain injuries and delayed cerebral ischemia, further increasing the risk of a poor outcome. In recent years, the renin–angiotensin system (RAS) has been proposed as a target pathway for therapeutic interventions after brain injury. The RAS is a complex system of biochemical reactions critical for several systemic functions, namely, inflammation, vascular tone, endothelial activation, water balance, fibrosis, and apoptosis. The RAS system is classically divided into a pro-inflammatory axis, mediated by angiotensin (Ang)-II and its specific receptor AT1R, and a counterbalancing system, presented in humans as Ang-(1–7) and its receptor, MasR. Experimental data suggest that upregulation of the Ang-(1–7)/MasR axis might be neuroprotective in numerous pathological conditions, namely, ischemic stroke, cognitive disorders, Parkinson’s disease, and depression. In the presence of SAH, Ang-(1–7)/MasR neuroprotective and modulating properties could help reduce brain damage by acting on neuroinflammation, and through direct vascular and anti-thrombotic effects. Here we review the role of RAS in brain ischemia, with specific focus on SAH and the therapeutic potential of Ang-(1–7).